A aprendizagem dos verbos pretérito perfecto simple e compuesto em espanhol: um estudo com foco na forma - Peruzzo, Chaiane (2023)
The research's theme is the learning and uses of verbs in the Pretérito Perfecto Simple and Pretérito Perfecto Compuesto in Spanish, based on a pedagogical intervention, based on Form-Focused Instruction, carried out with students in the 2nd year of high school. in the Spanish Language discipline. The general objective of this work is to verify the effect of the pedagogical intervention on the learning of Pretérito Perfecto Simple and Pretérito Perfecto Compuesto for high school students in Spanish. To this end, its specific objectives are: i) to develop and apply the analysis instruments: pre-test and immediate post-test; ii) plan and apply the pedagogical intervention to help students understand the use of verbs in Pretérito Simple and Pretérito Perfecto Compuesto in Spanish; and iii) analyze the results obtained from theoretical references based on Form-Focused Instruction. Therefore, the theory is anchored in Long (1991), Spada (1997), Ellis (2005), Sharwood Smith (1994), Schmidt (1990) and Krashen (1985), and aims to focus on the content being studied and the meaning it has for the student. The study is justified because, in Spanish, verbs in the past are used in two ways and, therefore, these two possibilities can cause doubts for students: one is used in the same way in Portuguese, it is the Past Tense Perfecto Simple or also called Indefinite; the other is formed by the verb haber plus participle of the main verb, this is the Pretérito Perfecto Compuesto. The results showed that students found it easier to develop controlled, multiple-choice activities than free activities in which they needed to conjugate the verb appropriately in each sentence, since in the controlled activity students got more correct answers compared to the free activity. both in the pre-test and post-test. Regarding the intervention, it was found to be beneficial, as in the controlled pre-test activity the students achieved 35.38% correct answers, while in the free activity the students obtained 11.24% correct answers; on the other hand, in the controlled post-test activity, the percentage of correct answers was 51.92% and in the free activity, it was 16.86%. Finally, it is important to emphasize that it is still important to continue studying foreign language teaching and learning to improve your teaching.